The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acsami.0c01819
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Effects of an Electrodeposited Copper Skin on the Strength and the Electrical and Thermal Conductivities of Reduced Graphene Oxide-Printed Scaffolds

Abstract: Architected Cu/rGO (reduced graphene oxide) heterostructures are achieved by electrodepositing copper on filament printed rGO scaffolds. The Cu coating perfectly contours the printed rGO structure, but isolated Cu particles also permeate inside the filaments. Although the Cu deposition conveys certain mass augment, the 3D structures remain reasonably light (bulk density  0.42 g cm -3 ). The electrical conductivity (e) of the Cu/rGO structure (8 x 10 4 S•m -1 ) shows a notable increment compared to e of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
(145 reference statements)
0
3
0
Order By: Relevance
“…The specimen section varies between 25 Â 25 and 40 Â 40 mm 2 , thus, similar to those used in TPS. Regarding additively manufactured 3D ceramic structures, to the best of the authors knowledge, there are no experimental works analysing their thermal conductivities, although comparative evaluations of the heat dissipation capability of different printed materials during cooling have recently been addressed [19][20][21][22].…”
Section: Thermal Conductivity Methodsmentioning
confidence: 99%
“…The specimen section varies between 25 Â 25 and 40 Â 40 mm 2 , thus, similar to those used in TPS. Regarding additively manufactured 3D ceramic structures, to the best of the authors knowledge, there are no experimental works analysing their thermal conductivities, although comparative evaluations of the heat dissipation capability of different printed materials during cooling have recently been addressed [19][20][21][22].…”
Section: Thermal Conductivity Methodsmentioning
confidence: 99%
“…weakness, air and flame exposure vulnerability, lack of porosity at different scales, etc) would entail making composites or hybrids by anchoring other species on the 3D graphene structure while maintaining the accessible porosity and cellular character [27][28][29]. In particular, our group has previously shown that via relatively simple methods, such as liquid infiltration with a preceramic polymer or via copper electrodeposition [30,31], it is possible to build complex composite and hybrid materials using printed GO scaffolds as templates/supports. Presently, we propose the infiltration of 3D printed reduced GO (rGO) structures with a well-known silica precursor, tetraethyl orthosilicate (TEOS) or alternatively, mixed with an Al2O3 precursor, and take advantage of the sol-gel route to build 3D silica/ silicoaluminate)/rGO hybrid materials that reproduce the 3D printed template.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Undoubtedly, graphene is an ideal additive for improving electric heating properties to electrical conductive composites. [11][12][13] With the development of graphene science, [14][15][16][17] graphene aerogel has proved to be one of the most promising materials for preparing electrical conductive materials because of its structural continuity, [18][19][20] where intermolecular bonding originated from π-π interactions and van der Waals forces between the graphene nanosheets. [21] In addition, graphene aerogels not only have a higher linkage density of nanosheets but also maintain excellent physicochemical properties of the 2D scale of graphene, which makes them more suitable to prepare functional composites.…”
Section: Introductionmentioning
confidence: 99%